Sistem Informasi Inventarisasi Sarana Dan Prasarana Berbasis Web Di Sekolah Menengah Atas Veteran Purwokerto - Sri Heneng Prasastono; Mohammad Hidayatul Holili (Universitas 17 Agustus 1945 Semarang, 2022)
The process of collecting data on facilities and infrastructure that is done manually will not run optimally. Conditions like this make an agency need an information system that is able to record all existing facilities and infrastructure, namely an inventory information system. The purpose of this research is to design and build a website-based inventory information system that is used to facilitate the process of inventorying or collecting data on goods at the Purwokerto Veteran High School. The MVC (Model View Controller) method is used to design the system. This system can simplify the process of collecting data on consumables (inventory), consumables (non-inventory), procurement, discrepancies, repairs and retrieval and this system can generate reports that will be reported to the Principal.